Islamic Moral Economy And Corporate Social Responsibility: Reframing Business Ethics In Muslim Enterprises - Sumpena, Mochamad (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2025)
This study examines how Islamic Moral Economy (IME) influences Corporate Social Responsibility (CSR) in Muslim companies by embedding moral and ethical values into core business responsibilities. Grounded in IME and maqasid al-shariah, and informed by comparisons with conventional CSR models such as Carroll’s CSR Pyramid and stakeholder theory, the study addresses limited attention to Islamic ethical foundations in mainstream CSR literature. Using a qualitative multiple-case study approach, it analyzes two Indonesian Muslim companies from different sectors: Bank Muamalat Indonesia in Islamic banking and Semen Indonesia in manufacturing. Data were gathered through semi-structured, in-depth interviews with managers and CSR practitioners, supported by analysis of corporate CSR documents. Thematic analysis was applied through inductive coding, theme development, and cross-case comparison. Findings reveal that IME-based CSR goes beyond philanthropic or reputational motives by prioritizing justice (‘adl), balance (mizan), and social welfare (maslahah) as core business objectives. However, tensions between commitments and profitability persist.